2006
DOI: 10.1136/jech.2005.039131
|View full text |Cite
|
Sign up to set email alerts
|

Validity of self reported diagnoses of cancer in a major Spanish prospective cohort study

Abstract: Introduction: This study aims to assess the validity of self reported diagnoses of cancer by persons recruited for the Spanish EPIC (European prospective investigation into cancer and nutrition) cohort study and to identify variables associated with correctly reporting a diagnosis of cancer. Methods: 41 440 members of EPIC were asked at the time of recruitment whether they had been diagnosed with cancer and the year of diagnosis and site. The process of validating self reported diagnoses of cancer included com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
47
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(65 citation statements)
references
References 29 publications
14
47
4
Order By: Relevance
“…Similarly, this study shows a moderately high sensitivity for prostate cancer, possibly reflecting an increased public awareness of prostate cancer within the last decade 18 . Our study demonstrated much higher sensitivity for bowel cancer as compared to previous studies in Spain (17.4%) 19 and Japan (14%) 20 . This may be due to the nation‐wide implementation of bowel cancer awareness by health authorities as it is the second most common cancer in Australia 13…”
Section: Discussionsupporting
confidence: 63%
“…Similarly, this study shows a moderately high sensitivity for prostate cancer, possibly reflecting an increased public awareness of prostate cancer within the last decade 18 . Our study demonstrated much higher sensitivity for bowel cancer as compared to previous studies in Spain (17.4%) 19 and Japan (14%) 20 . This may be due to the nation‐wide implementation of bowel cancer awareness by health authorities as it is the second most common cancer in Australia 13…”
Section: Discussionsupporting
confidence: 63%
“…Such documentation was obtained for only 34 (25.6%) of the CCa cases, but these records confirmed 97% of the CCa diagnoses in this subset. Previous studies have found from 17 – 100% of self-reported CCa52,53 and 48 – 93% of first-degree relative-reported CCa were confirmed by medical records54,55. Therefore, there may be individuals with CCa that were missed or, more rarely, individuals with an incorrect assignment of CCa.…”
Section: Discussionmentioning
confidence: 97%
“…However, this means that our cancer variable is most likely conservative. The validity of self-reported cancer is likely to vary based on the cancer type diagnosed, and tends towards an underreporting of cancers, given the high levels of specificity reported in studies comparing self-reports to registry data [31]. Indeed in studies where cancer registry data have been compared to self-reported information individuals tend to underreport rather than overreport cancer history, and variation in inaccurate cancer reporting varied considerably by cancer type [32].…”
Section: Discussionmentioning
confidence: 99%
“…The probability of misreporting cancer, both over-reporting and under-reporting, has been associated with socio-demographic characteristics: gender, age, BMI, size of household, place of birth, smoking, social participation, educational level, type of employment, alcohol consumption and poor well-being [34]. The sensitivity of self-reported cancer is also likely to be higher among respondents with a high level of education [31]. Stavrou et al have demonstrated a good level of sensitivity and specificity for self-reported cancer diagnoses in a cohort of older women in Australia, comparing self-reports to registry data [35].…”
Section: Discussionmentioning
confidence: 99%